1993
DOI: 10.1111/j.1600-051x.1993.tb00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of adjunctive minocycline‐HCI to eliminate oral Actinobacillus actinomycetemcomitans

Abstract: Considerable problems have been reported in the eradication of Actinobacillus actinomycetemcomitans from periodontal sites. The present communication describes the 2-year results of a comprehensive combined mechanical/surgical and adjunctive minocycline (200 mg/day for 3 and another 2 weeks) treatment regimen in 28 patients with A. actinomycetemcomitans-associated periodontitis. Elimination of A. actinomycetemcomitans at periodontal sites was a prerequisite for gain of clinical attachment of > or = 2 mm or dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Thus, when the gingival status was compared between Group A and Group B, a significant improvement was observed on day 30, day 90, and day 180 in the test sites [Graph 2]. This is consistent with the findings of the studies conducted by Muller et al .,[17] Vansteenberghe et al .,[10] Saito et al .,[12] Jones et al .,[13] Timmerman et al .,[14] Radvar et al ,[18] Hagiwara et al .,[15] Vansteenberghe et al .,[16] and Kinane et al . [19]…”
Section: Discussionsupporting
confidence: 88%
“…Thus, when the gingival status was compared between Group A and Group B, a significant improvement was observed on day 30, day 90, and day 180 in the test sites [Graph 2]. This is consistent with the findings of the studies conducted by Muller et al .,[17] Vansteenberghe et al .,[10] Saito et al .,[12] Jones et al .,[13] Timmerman et al .,[14] Radvar et al ,[18] Hagiwara et al .,[15] Vansteenberghe et al .,[16] and Kinane et al . [19]…”
Section: Discussionsupporting
confidence: 88%
“…Local therapy presupposes that the infection is limited to the clinically diagnosed lesion. Bacteria typically associated with periodontal lesions can, however, also be detected in clinically unaffected regions of the dentition [2, 3] and non-dental sites, such as the dorsum of the tongue or tonsillar crypts [4][5][6][7][8]. Systemic adverse drug reactions, on the other hand, are a greater concern and more likely to occur if drugs are distributed via the systemic route.…”
Section: What Options Do We Have?mentioning
confidence: 99%
“…Identification of these microorganisms in periodontal patients with the help of commercially available gene probe tests has become a clinical valuable tool in treatment planning and in the selection of adjunctive antibiotics. In patients who tested positive for A.a., it could be shown that the mechanical removal of the subgingival biofilm alone did not ensure a reliable and predictable treatment outcome [5][6][7]. Furthermore, it was shown that A.a. plays a crucial role in the aetiology of severe chronic periodontitis, aggressive periodontitis [8][9][10] and periodontitis as a manifestation of Papillon Lefèvre syndrome [11].…”
Section: Introductionmentioning
confidence: 98%